Heartbeat and body temperature monitoring device using IOT / Nik Nur Amira R. Azmi - R. Azmi, Nik Nur Amira (2024)
With wide exposure to the Internet of Things (IoT), it has changed the way healthcare workers monitor patients. The elderly citizen going to the healthcare centre for a medical checkup regularly, but this can be reduced by only using smart device at home. This project aims to develop a prototype of a heartbeat and body temperature monitoring device. The projects also construct an IoT-based technology control system using thingSpeak. The designed hardware consists of a heartbeat sensor, temperature sensor, and thingSpeak as its IoT platform. As the outcome, the sensors detect their reading and prompt the value on the screen, then the health status is in normal, dangerous or need to take some rest. This monitoring system allows medical providers to remotely observe their patients who are particularly those with chronic diseases related to the heart. Additionally, the size of this device is compact, user-friendly, and easy to bring anywhere. Moreover, the data will be transmitted to an application. In the future enhancement, the user will be able to retrieve the data stored in the application. Because of that, it reduces the need for repeated trips to the hospital